التضاد في القرآن الكريم عند علي الخولى - Malia Fransisca (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2019)
Abstract Al-Qur’an is kalamullah revealed to the Prophet Muhammad SAW through the angel Jibril using Arabic. Al-Qur’an is a guide to the life of Muslims. Therefore, all Muslims must learn the Qur’an from how to read it to understanding is content. The knowledge used to learn how to read al-Qur’an is Tajwid. To find out the meaning of the contents of al-Qur’an must master the vocabulary in Arabic or better knows as mufrodat. No less important, to understand this holy book, we need to know the rules of Arabic science such as Nahwu, Shorf and Dilalah. Dilalah Knowledge becomes important to learn because to find out the meaning of the contents of al-Qur’an. One discussion of Dilalah Science. Therefore, in this article we will expain how the antonym in Surah al-Mulk/ Tabarak uses the theory of Ali al-Khuli. According to Ali al-Khuli there are 9 types of antonym, namely: Binary Antonym, Reserve Antonym, Gradual Antonym, Vertical Antonym, Extensional Antonym, Partial Antonym, Cyclic Antonym, Rank Antonym, and Affinity Antonym. But in Surah al-Mulk there are only 3 types of antonyms based on the division of Ali al-Khuli, namely: Binary Antonym, Partial Antonym and Affinity Antonym. Keywords : Antonym, Al-Qur’an